Porcine circovirus type 2 and porcine reproductive and respiratory syndrome virus alone or associated are frequent intralesional detected viruses in porcine respiratory disease complex cases in Northern Italy - Giulia D’Annunzio; Giulia D’Annunzio; Fabio Ostanello; Luisa Vera Muscatello; Massimo Orioles; Niccolò Jacumin; Nicola Tommasini; Giorgio Leotti; Andrea Luppi; Luciana Mandrioli; Giuseppe Sarli (Frontiers in Veterinary Science, 2023)
MethodsThis study aimed to examine the pathological impact of Porcine Circovirus type 2 (PCV2) and Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) through histological and immunohistochemical analysis of 79 cases of Porcine Respiratory Disease Complex (PRDC) collected from 22 farms in Northern Italy. Lung tissue and several lymphoid organ samples were deployed to associate PCV2-positive stain with Circovirus-associated Diseases (PCVD).ResultsThe most common lung lesion observed was interstitial pneumonia, alone or combined with bronchopneumonia. By immunohistochemistry, 44 lungs (55.7%) tested positive for PCV2, 34 (43.0%) for PRRSV, 16 (20.3%) for both viruses and in 17 cases (21.5%) neither virus was detected. Twenty-eight out of 44 (63.6%) PCV2-positive cases had lymphoid depletion or granulomatous inflammation in at least one of the lymphoid tissues examined; thus, they were classified as PCV2 Systemic Diseases (PCV2-SD). In the remaining 16 out of 44 cases (36.4%), PCV2-positive lung lesions were associated with hyperplastic or normal lymphoid tissues, which showed PCV2-positive centrofollicular dendritic cells in at least one of the lymphoid tissues examined. Therefore, these cases were classified as PRDC/PCV2-positive. In the PCV2-positive animals, 42.9% of the PCV2-SD cases (12/28) showed immunohistochemistry (IHC) positivity for PRRSV in the lung tissue, while 25.0% of PRDC/PCV2-positive cases (4/16) showed double positivity for PCV2 and PRRSV.DiscussionIn light of the caseload presented in this study, characterized by the high proportion of PCV2-SD cases alongside the overall respiratory symptomatology, it is imperative to emphasize the crucial role of a comprehensive sampling protocol. This is critical to avoid underestimating the harm caused by PCV2 in farms, particularly with respect to the systemic form of the disease. PCV2 and PRRSV remain the primary infections associated with PRDC in Italy that can significantly impact farm health and co-infections in the field can worsen the pathology, thus the selection of appropriate preventive measures is critical.